Strategi Perencanaan SI/TI pada Perusahaan Waralaba (Studi Kasus: PT. GBR) - Fernanda Wijaya Kusuma (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
PT. GBR is a company in the field of men's haircut services with the brand name X Barbershop which has a vision becoming the number one company that houses the best barbershops and barbershop franchises in Indonesia. Companies have utilized IT in their business processes, however, to further enhance their competitive advantage, a plan is needed to maximize the utilization of IT in order to achieve the vision desired by the company. IS planning strategy research was carried out using the Ward and Peppard method to analyze the company’s internal and external environment. The tools used are SWOT, BSC, CSF, PESTEL. The results of this research is a Future Application Portfolio and application proposals are divided into four quadrants, namely Key Operational including SI Kepegawaian, Absensi Fingerprint, SI Manajemen, SI Keuangan, Support including E-Learning, Cloud Backup, Strategic including CRM, SI Survei Kepuasan Pelanggan, and High Potential including SI Jaminan Mutu. Keywords: Planning Strategy , Ward and Peppard, Future Application Portfolio, Internal and External Environment Analysis